Power Balance: Hacking Accountability from a Foucauldian Perspective - Widyatama, Arif (STIE Madani Balikpapan, 2024)
This article aims to convey an accountability perspective from the Foucauldian viewpoint. The research utilizes a literature review approach based on bibliographic sources, thus the data employed are bibliographic in nature. The findings indicate that when SMEs are unable to implement accountability measures, they may face punishments, whether from third parties such as banks when seeking capital for business development, or from the government regarding tax reporting, which may lead to government enforcement if SMEs fail to comply with the applicable SAK ETAP regulations. Therefore, an appropriate approach or method is necessary to assist and enhance the accountability quality of SMEs.